2019
DOI: 10.1186/s12913-019-4078-1
|View full text |Cite
|
Sign up to set email alerts
|

Building general practice training capacity in rural and remote Australia with underserved primary care services: a qualitative investigation

Abstract: Background Australians living in rural and remote areas have access to considerably fewer doctors compared with populations in major cities. Despite plentiful, descriptive data about what attracts and retains doctors to rural practice, more evidence is needed which informs actions to address these issues, particularly in remote areas. This study aimed to explore the factors influencing General Practitioners (GPs), primary care doctors, and those training to become GPs (registrars) to work and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 17 publications
(14 reference statements)
3
36
0
1
Order By: Relevance
“…Of the scant literature on this topic, one study [13] interviewed rural GP supervisors in NSW and Victoria, not restricted to rural settings, finding that GPs are motivated to supervise by personal and professional factors, including professional development reasons, and because it was rewarding. A further study to inform growth of GP training in remote Queensland identified that supervising GP registrars in remote communities could be a way to enable unique high quality and team-based learning but practice busy-ness was a concern [14].…”
Section: Introductionmentioning
confidence: 99%
“…Of the scant literature on this topic, one study [13] interviewed rural GP supervisors in NSW and Victoria, not restricted to rural settings, finding that GPs are motivated to supervise by personal and professional factors, including professional development reasons, and because it was rewarding. A further study to inform growth of GP training in remote Queensland identified that supervising GP registrars in remote communities could be a way to enable unique high quality and team-based learning but practice busy-ness was a concern [14].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 As well as serving workforce imperatives, rural GP training offers particular training experiences 7 including increased exposure to complex medical and surgical care, 8 as well as unique learning experiences for registrars, including increased scope of practice. 9 Rural practice might also entail considerable challenges and stress for registrars, including perceived greater workload and responsibility, 7 burnout 9 and perceived higher risk of occupational violence. 10 Understanding the epidemiology of registrars' training experience in rural and regional areas, compared to urban areas, is important for Australian GP training and for rural communities.…”
mentioning
confidence: 99%
“…Many (14) participants undertook supervision in the hope of securing a doctor to support their succession planning, but there were few instances where this directly occurred. One participant, considering the seemingly insurmountable di culties of recruiting doctors to remote Tasmania, re ected "you can't conscript … I'd like to, but [we're] not allowed to" (#6, <5 FTE, remote).…”
Section: Patient Accessmentioning
confidence: 99%
“…Of the scant literature on this topic, one study (13) interviewed rural GP supervisors in NSW and Victoria, not restricted to rural settings, nding that GPs are motivated to supervise by personal and professional factors, including professional development reasons, and because it was rewarding. A further study to inform growth of GP training in remote Queensland identi ed that supervising GP registrars in remote communities could be a way to enable unique high quality and team-based learning but practice busy-ness was a concern (14).…”
Section: Introductionmentioning
confidence: 99%